Identification of key gene networks controlling organic acid and sugar metabolism during watermelon fruit development by integrating metabolic phenotypes and gene expression profiles. (1st December 2020) - Umer, Muhammad Jawad; Bin Safdar, Luqman; Gebremeskel, Haileslassie; Zhao, Shengjie; Yuan, Pingli; Zhu, Hongju; Kaseb, M O; Anees, Muhammad; Lu, Xuqiang; He, Nan; Gong, Chengsheng; Liu, Wenge
Abstract: The organoleptic qualities of watermelon fruit are defined by the sugar and organic acid contents, which undergo considerable variations during development and maturation. The molecular mechanisms underlying these variations remain unclear. In this study, we used transcriptome profiles to investigate the coexpression patterns of gene networks associated with sugar and organic acid metabolism. We identified 3 gene networks/modules containing 2443 genes highly correlated with sugars and organic acids. Within these modules, based on intramodular significance and Reverse Transcription Quantitative polymerase chain reaction (RT-qPCR), we identified 7 genes involved in the metabolism of sugars and organic acids. Among these genes, Cla97C01G000640, Cla97C05G087120 and Cla97C01G018840 ( r 2 = 0.83 with glucose content) were identified as sugar transporters ( SWEET, EDR6 and STP ) and Cla97C03G064990 ( r 2 = 0.92 with sucrose content) was identified as a sucrose synthase from information available for other crops. Similarly, Cla97C07G128420, Cla97C03G068240 and Cla97C01G008870, having strong correlations with malic ( r 2 = 0.75) and citric acid ( r 2 = 0.85), were annotated as malate and citrate transporters ( ALMT7, CS, and ICDH ). The expression profiles of these 7 genes in diverse watermelon genotypes revealed consistent patterns of expression variation in various types of watermelon. These findings add significantly to our existing knowledge of sugar and organic acid metabolism in watermelon.